Pengaruh Manajemen Laba dan Price Earning Ratio Terhadap Nilai Perusahaan dengan Free Cash Flow sebagai Variabel Moderasi pada Perusahaan Manufaktur Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia - aprillio try bimo (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2018)
The purpose of this study was to analyzed how much influence of earnings management, price earning ratio an affect firm value, as well as analyzed free cash flow strengthen or weaken the influence of earning management on firm value and free cash flow strengthen or weaken the influence of price earning ratio on firm value that listed at pharmaceutical companies in Indonesian Stock Exchange period of 2010-2016. This study used secondary data obtained from IDX website with data collection method of purposive sampling then obtained 49 data sample research. Method of data analysis in this research is multiple linear regression analysis. The result of this study is earnings management has a significant positive effect on firm value, price earning ratio has a significant positive effect on firm value, Free cash flow can not serve as a moderating variable that affects earning management, but directly act as independent variables that significantly influence the value of the company, and the influence of price earning ratio on firm value is weaken by free cash flow. The results of this study obtained R square value of 0.753 which means the closeness of the firm value with two variable independent is strong.